A comparative evaluation of standard and balloon-assisted coiling of intracranial aneurysms based on neurophysiological monitoring - Waldeck, Stephan; Chapot, René; Falck, Christian von; Froelich, Matthias F.; Brockmann, Marc Alexander; Overhoff, Daniel (Journal of Clinical Medicine, 2022)
Background and purpose: Intracranial aneurysms are commonly treated with balloon-assisted endovascular coiling because the balloon allows for the control und modulation of wide-necked aneurysms and the coil basket. However, this approach might be associated with a higher complication rate. This retrospective study compared the multimodal results between balloon-assisted coiling of aneurysms (group 1) and coiling without balloon assistance (group 2). Materials and Methods: We included 67 patients with unruptured intracranial aneurysms in this retrospective analysis; acutely ruptured aneurysms were excluded from the analysis. We divided these patients into two groups and evaluated them for symptomatic thromboembolic complications in the course of intracranial aneurysm treatment. All patients had an intrainterventional neurophysiological monitoring (IINM) and a pre- and postinterventional NIH Stoke Scale (NIHSS) survey and MR imaging. Multiple logistic regression was used to assess whether balloon-assisted coiling increased the rate of thromboembolic complications. Periprocedural aneurysm hemorrhage did not occur in any of the cases. Results: We detected no statistically significant difference in rates of neurophysiological disturbances (19.5% (group 1) versus 34.6% (group 2); p = 0.249). There was no association with age, gender, or aneurysm location. The occurrence of new diffusion-weighted defects was not statistically significantly different (19.5% (group 1) versus 35.0% (group 2); p = 0.166). The difference in NIHSS before and after the intervention showed also no statistical significance in both groups (p = 0.426). Conclusion: The use of balloon-assisted coiling did not increase the rate of neurological disturbances during endovascular coiling. MR imaging and NIHSS survey also showed no increased risk of embolization from balloon-assisted aneurysm coiling. IINM is a central aspect of care during endovascular coiling as it can substantially decrease morbidity.